2016
DOI: 10.1111/jace.14599
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Al and Na in Hydrothermally Synthesized Tobermorite

Abstract: Calcium silicate hydrate and its Al‐substituted form synthesized by a hydrothermal process were investigated by X‐ray diffraction, compositional analysis, and magic‐angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy, in order to determine the mechanism of Al and Na incorporation in the tobermorite structure with varying molar ratios of Ca/Si and Al/Si. At a high molar ratio of Ca/Si, the silicate chains of tobermorite are ruptured, the degree of polymerization of the silicate chains is lowered, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 38 publications
(232 reference statements)
2
24
0
Order By: Relevance
“…At low Ca/Si ratios (≤0.8), aluminum was observed mainly as tetrahedrally coordinated Al(IV), and low aqueous aluminum concentrations (below the detection limit) indicated a high affinity of aluminum toward the C‐S‐H phase. The previous works are generally in agreement with our NMR results and with the recent solid‐state 29 Si and 27 Al MAS NMR spectroscopy study presented by Wang et al . These authors showed that tetrahedrally coordinated Al (Al(IV)) could either act as bridging tetrahedron for the tobermorite chains or be present in the Q 3 sites that link 2 chains together …”
Section: Discussionsupporting
confidence: 93%
“…At low Ca/Si ratios (≤0.8), aluminum was observed mainly as tetrahedrally coordinated Al(IV), and low aqueous aluminum concentrations (below the detection limit) indicated a high affinity of aluminum toward the C‐S‐H phase. The previous works are generally in agreement with our NMR results and with the recent solid‐state 29 Si and 27 Al MAS NMR spectroscopy study presented by Wang et al . These authors showed that tetrahedrally coordinated Al (Al(IV)) could either act as bridging tetrahedron for the tobermorite chains or be present in the Q 3 sites that link 2 chains together …”
Section: Discussionsupporting
confidence: 93%
“…AB can be easily transformed to the gas phase through the formation of droplets at moderate temperature without the need of catalyst [30,59,60]. In particular, AB has been investigated as a precursor of BN nanospheres through a vapor phase pyrolysis procedure using two independently temperature-controlled furnaces coupled with a conventional treatment at 1300-1700 8C [59].…”
Section: Nanostructured and Architectured Bn One-step Synthesis Of Bnmentioning
confidence: 99%
“…PBZ is synthesized with controlled cross-linking degrees by selfcondensation of BZ at a low temperature inside an autoclave. A large number of studies have been focused on the thermo-polymerization of BZ and the identification of polymerization mechanisms [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. In the sixties, several authors studied the selfcondensation of BZ forming biphenylic and naphtalenic-type structures (Fig.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Due to their excellent thermal and mechanical properties at high temperatures and due to their low material density, they will increase the payload capacity and improve the performance of future upper-stage and orbital rocket engines. [1][2][3][4][5] A variety of different ceramic matrix composite (CMC) processing routes have been studied intensively during the last 10 years, including chemical vapor infiltration (CVI), [6][7][8][9] liquid polymer infiltration and pyrolysis (PIP), 10,11 and reactive melt infiltration, [12][13][14][15][16] and combinations of these. Processing costs and durations are significantly high using CVI or PIP fabrication routes.…”
Section: Introductionmentioning
confidence: 99%